Impact of silkworm pupae (Bombyx mori) powder on cream foaming, ice cream properties and palatability. (January 2022) - David-Birman, Tatyana; Romano, Alon; Aga, Aseel; Pascoviche, Dafna; Davidovich-Pinhas, Maya; Lesmes, Uri
Abstract: Food fortification with edible insects can offer high nutritional values, improve consumer acceptance and sustainability of resources. This study elucidates the ramifications of silkworm pupae flour (SWF), i.e. dried and pulverized, on the rheological, textural, and sensorial properties of whipping and ice-cream. Results indicate SWF supplementation attenuates cream overrun (p < 0.05) with an observed viscosity increase. Contrary, SWF addition reduced (p < 0.05) separation of foam implying a shelf-life improvement. SWF enriched ice-cream exhibited altered texture attributes (hardness and adhesiveness) especially when using more than 1% (w/w) SWF. In addition, a notable effect on product color was registered which explains the reduced visual appeal of ice-creams containing 2.5% and 4% (w/w) SWF. Moreover, an untrained tasting panel (mean age: 28.6 ± 8.6) reported a strong aftertaste. Overall, this study concludes that SWF at concentrations of ≤1% (w/w) can enhance ice-cream techno-functional properties while maintaining palatability. Industrial relevance: Edible insects are a promising, cost-effective and highly sustainable food resource for proteins and other macro and micro-nutrients. Besides their nutritional advantages, they possess potential techno-functional properties that persist during processing operations and comply with various food matrices. This study offers an original use of bombyx Mori powder, to foam applications, like whipped cream and ice cream. Although not devoid of a on ice cream sensorial attributes, it is still palatable as ascertained by a tasting panel of 40 adult volunteers. Highlights: Silkworm pupae flour (SWF) was incorporated into whipped cream and ice cream. SWF supplementation reduced cream overrun with an observed viscosity increase. SWF addition reduced cream separation of foam implying a shelf- life improvement. Texture analysis revealed significant changes in hardness and adhesiveness. SWF addition reduced ice cream's overall appearance.